(untitled) (Palíndromo, 2020)
This article presents a bibliographical search carried out in the Annals of the National Meetings of the National Association of Graduate Studies and Research in Education (Anped), in the period of 2007-2017, in order to identify the production on Visual Culture that is being constructed in Brazil. The data collection was carried out from two descriptors: visual culture and visuality. Seven papers with descriptors were found in the title, abstract or keywords of the communications, of which three focused on issues related to teacher training; two of it discusses Formal and Non-Formal Education, one of it addresses Special Education and the other highlights the visual experience within Basic Education. The results indicate that the problem of visuality and the social construction of vision are still emerging in the GT 24 of Anped, signaling research gaps on the visual construction of the social, within a culture abounding visual phenomena and acts